Preparation method and application of NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics
By forming a NiCo2O4/MnO2 composite catalyst layer on the electrode, the existing electrodes have high cost, poor corrosion resistance and insufficient degradation ability in the treatment of antibiotic wastewater, and achieve efficient antibiotic degradation and long-life stability of the electrode.
Patent Information
- Application Number
- CN202411901171.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
AI Technical Summary
The existing electrodes have high preparation cost, poor corrosion resistance and insufficient degradation ability in antibiotic wastewater treatment.
The preparation method of NiCo2O4/MnO2 composite catalyst electrode is adopted, and the NiCo2O4 intermediate layer and MnO2 outer layer are formed on metal or alloy substrates through electrodeposition technology, combining the high conductivity of NiCo2O4 and the strong oxidation ability of MnO2.
The degradation efficiency of antibiotics is significantly improved, with a degradation rate of up to 89.4% to 99.1%, and the acceleration life time of the electrode is extended under extreme conditions, improving stability and corrosion resistance.
Smart Images

Figure CN119776941A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a catalyst electrode for electrocatalytic degradation of antibiotics. Background Art
[0002] If antibiotic wastewater is discharged into the environment without treatment, it will cause serious deterioration of the ecosystem. Antibiotic wastewater has strong antibacterial properties and complex components, and it is difficult to remove it through traditional biological oxidation, microbial degradation, photodegradation, activated carbon uniform coagulation or adsorption methods. Electrochemical methods have attracted much attention in the field of antibiotic wastewater treatment due to their advantages such as strong oxidation ability, high controllability, mild reaction conditions, small footprint and environmental friendliness.
[0003] With the rapid development of science and technology and industrialization, traditional anode materials have shown more and more limitations. For example, the cost of platinum electrodes is too high, and the corrosion resistance of graphite-based electrodes is poor. They can no longer meet the needs of modern industry for low consumption and high output, low investment and high return, and green environmental protection and no pollution. Therefore, it is urgent to find a new type of anode material that is low-cost, corrosion-resistant, has good performance, strong catalytic ability and is environmentally friendly. At present, researchers have doped Bi in the active coating of the electrode. 3+ 、Co 2+ 、Ce 3+ ,La 3+ , Fe 3+ 、Co 2+ Some special ions such as metal ions can be used to improve the electrocatalytic activity of the electrode and enhance the degradation ability of organic pollutants by utilizing the conductivity and catalytic activity of metal ions. However, the improvement of the electrocatalytic performance of the catalyst prepared by the above method is limited. Summary of the invention
[0004] The present invention aims to solve the technical problems of high preparation cost, poor corrosion resistance and poor degradation ability of existing electrodes, and provides a method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics.
[0005] The preparation method of the NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics of the present invention is carried out according to the following steps:
[0006] 1. First, the metal or alloy substrate is degreased and the surface oxide layer is removed in sequence, and then ultrasonically cleaned with deionized water to obtain a clean substrate;
[0007] 2. Mixing a metal salt, an ammonium salt and a solvent and stirring them to obtain an electrodeposition solution A; wherein the metal salt is a cobalt salt and a nickel salt;
[0008] 3. mixing the manganese salt, the sulfate and the solvent and stirring them to obtain an electrodeposition solution B;
[0009] 4. Preparation of NiCo2O4 intermediate layer: using a clean substrate as cathode and a titanium sheet as anode, electrodeposition is performed in electrodeposition solution A; after the electrodeposition process is completed, the electrode is cleaned with clean water and dried to obtain an electrode sheet loaded with a precursor; then the electrode sheet loaded with a precursor is placed in a muffle furnace and calcined at a temperature of 200°C to 500°C for 1h to 5h to obtain an electrode sheet loaded with a NiCo2O4 catalyst;
[0010] 5. Preparation of MnO2 layer: Using the electrode sheet loaded with NiCo2O4 catalyst as the anode and the platinum sheet as the cathode, electrodeposition is carried out in the electrodeposition solution B. After the electrodeposition process is completed, the electrode is cleaned with clean water and dried to obtain a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics.
[0011] Furthermore, the metal or alloy substrate described in step 1 is one or more of Ti, Fe, and stainless steel substrates in different forms.
[0012] Furthermore, the substrate cleaning method described in step one is one or more of alkaline cleaning, ultrasonic cleaning, steam degreasing and acid cleaning.
[0013] Furthermore, the cobalt salt described in step 2 is Co(NO3) 2、 One or more of CoCl2, CoSO4 and CoF2.
[0014] The nickel salt is one or more of NiCl2, Ni(NO3)2 and NiSO4.
[0015] Furthermore, the ammonium salt described in step 2 is one or more of NH4F, NH4NO3 and NH4NO2.
[0016] Furthermore, the nickel salt in step 2 is 2+ 、Co in cobalt salts 2+ 、NH4 in ammonium salt + The molar ratio of the substance is (0.01~10)mmol:(0.02~20)mmol:(0.1~100)mmol.
[0017] Furthermore, the nickel salt in step 2 is 2+ The ratio of the amount of substance to the volume of the solvent is (0.01~10)mmol:(10~1000)mL.
[0018] Furthermore, the solvent in step 2 is one or more of deionized water, ethanol and methanol.
[0019] Furthermore, the manganese salt (Mn 2+ ) is one or more of MnSO4, Mn(NO3)2, and MnCl2.
[0020] Furthermore, the sulfate (SO4 2- ) is one or more of Na2SO4, K2SO4, and (NH4)2SO4.
[0021] Furthermore, the Mn in the manganese salt described in step 3 2+ SO4 in sulfate 2- The molar ratio of the substance is (0.01~20)mmol:(0.1~100)mmol.
[0022] Furthermore, the Mn in the manganese salt described in step 3 2+ The ratio of the amount of substance to the volume of the solvent is (0.01~20)mmol:(10~1000)mL.
[0023] Furthermore, the stirring speed in step three is 50-400 r / min, and the stirring time is 50-180 min.
[0024] Furthermore, the solvent in step three is one or more of deionized water, ethanol and methanol.
[0025] Furthermore, during the electrodeposition described in step 4, the distance between the anode and the cathode is 2 to 3 cm.
[0026] Furthermore, the electrodeposition described in step 4 is carried out by constant current electrodeposition, and the constant current is controlled to be 1-50 mA / cm 2 The electrodeposition time is 20 to 25 minutes, and the electrodeposition temperature is 20 to 50°C.
[0027] Furthermore, the drying in step 4 is carried out at a temperature of 50° C. to 100° C. for 1 to 3 hours.
[0028] Furthermore, the calcination temperature in step 4 is 200° C. to 500° C. for 1 to 5 hours.
[0029] Furthermore, during the electrodeposition described in step five, the distance between the anode and the cathode is 2 to 3 cm.
[0030] Furthermore, the electrodeposition described in step 5 is carried out by constant current electrodeposition, and the constant current is controlled to be 5-60 mA / cm 2 The electrodeposition time is 30 to 35 minutes, and the electrodeposition temperature is 20 to 50°C.
[0031] Furthermore, the drying in step 5 is carried out at a temperature of 50° C. to 100° C. for 1 to 3 hours.
[0032] The application of the NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics prepared by the above method is to use the NiCo2O4 / MnO2 composite catalyst electrode in the degradation of antibiotics.
[0033] The NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics prepared by the present invention combines the advantages of NiCo2O4 and MnO2. The high conductivity of NiCo2O4 and the strong oxidizing ability of MnO2 work together to greatly improve the efficiency of the composite catalyst in degrading antibiotics. The antibiotic degradation efficiency can reach 89.4% to 99.1% when the electrocatalytic degradation is carried out for 120 minutes, and the composite catalyst electrode has excellent stability and long life. Compared with a single NiCo2O4 catalyst electrode and a MnO2 catalyst electrode, under extreme conditions of a current density of 500 mA·cm-2 and a pH value of 1, the accelerated life time is increased by 3.7 times and 1.9 times, respectively.
[0034] The NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics prepared by the present invention has high degradation performance, good corrosion resistance, good stability, strong oxidation ability, low energy consumption, small footprint and environmental friendliness; its preparation process is simple and easy to operate, low cost, small equipment investment, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1;
[0036] Figure 2 XRD spectrum of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1;
[0037] Figure 3 This is a degradation performance diagram of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1;
[0038] Figure 4 This is a scanning electron microscope image of the NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2;
[0039] Figure 5 This is a degradation performance diagram of the NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2;
[0040] Figure 6 This is a scanning electron microscope image of the NiCo2O4 catalyst electrode prepared in Comparative Example 1;
[0041] Figure 7 This is a degradation performance diagram of the NiCo2O4 catalyst electrode prepared in Comparative Example 1;
[0042] Figure 8 This is a scanning electron microscope image of the MnO2 electrocatalyst electrode prepared in Comparative Example 2;
[0043] Fig. 9 This is a degradation performance diagram of the MnO2 electrocatalyst electrode prepared in Comparative Example 2;
[0044] Fig.10 This is a graph showing the accelerated life test of different electrocatalyst electrodes under extremely harsh conditions. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The various raw materials used in the embodiments of the present invention are commercially available unless otherwise specified.
[0046] Example 1: The preparation method of the NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics in this example is carried out according to the following steps:
[0047] 1. Cut the Ti substrate into 1cm×3cm samples, immerse them in a constant temperature water bath filled with 40wt% sodium hydroxide solution to remove oil, take them out and use deionized water ultrasonic cleaning to obtain the deoiled Ti substrate; immerse the deoiled Ti substrate in a 10wt% oxalic acid solution for etching, take them out and use deionized water ultrasonic cleaning to obtain a clean Ti substrate;
[0048] 2. 3.75 mmol of cobalt chloride hexahydrate, 1.25 mmol of nickel sulfate hexahydrate, 10 mmol of ammonium chloride and 30 mL of deionized water were mixed, and stirred at a speed of 70 r / min for 30 min to obtain an electrodeposition solution A;
[0049] 3. Mix 7.5 mmol of anhydrous manganese sulfate, 15 mmol of sodium sulfate and 30 mL of deionized water, and stir at a speed of 70 r / min for 30 min to obtain an electrodeposition solution B;
[0050] Preparation of NiCo2O4 intermediate layer: With the clean Ti substrate as cathode and the titanium sheet as anode, the distance between the anode and cathode is 2 cm, and the electrodeposition is carried out in the electrodeposition solution A, wherein the current density during electrodeposition is 10 mA / cm 2, the electrodeposition time is 20min, the temperature during electrodeposition is 30℃, and the stirring speed during electrodeposition is 60r / min; after the electrodeposition procedure is completed, the electrode is cleaned with clean water and placed in an oven at a temperature of 60℃ for 2 hours to obtain an electrode sheet loaded with a precursor; then the electrode sheet loaded with a precursor is placed in a muffle furnace and calcined at a temperature of 300℃ for 3h to obtain an electrode sheet loaded with a NiCo2O4 catalyst;
[0051] 5. Preparation of MnO2 layer: The electrode sheet loaded with NiCo2O4 catalyst was used as anode and the platinum sheet was used as cathode. The distance between the anode and cathode was 2 cm. Electrodeposition was performed in electrodeposition solution B. The current density of electrodeposition was 15 mA / cm 2 ; The electrodeposition time was 30 min, the electrodeposition temperature was 50°C, and the stirring speed was 60 r / min; after the electrodeposition process was completed, the electrode was cleaned with clean water and dried in an oven at 50°C for 2 hours to obtain a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics, which was recorded as NiCo2O4 / MnO2-1;
[0052] Figure 1 The scanning electron microscope image of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1; Figure 1 It can be seen that under an electron microscope, the NiCo2O4 / MnO2 composite catalyst electrode prepared in Example 1 is composed of many nanosheets with a thickness of 5 to 10 nm, which increases the specific surface area of the catalyst, accelerates the degradation reaction rate, and the electrode surface is smooth and crack-free.
[0053] Figure 2 XRD pattern of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1; Figure 2 It can be seen that the components of the catalyst are NiCo2O4 and MnO2. The comparison results of the NiCo2O4 / MnO2 composite catalyst electrode and the standard card are consistent. The characteristic peaks show that NiCo2O4 and MnO2 have good crystallinity.
[0054] The degradation of antibiotic wastewater using the NiCo2O4 / MnO2 composite catalyst electrode prepared in Example 1 is specifically carried out in the following steps:
[0055] Preparation of tetracycline simulated wastewater: 50 mg of tetracycline solid and Na2SO4 are dissolved in 1 L of deionized water to obtain antibiotic wastewater; the mass fraction of Na2SO4 in the tetracycline simulated wastewater is 1%;
[0056] The NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1 was used as the anode and the stainless steel electrode was used as the cathode. The electrode was inserted into 50 mL of antibiotic wastewater and then heated to 15 mA / cm 2 The degradation was performed at a voltage of 50 V, and the degradation rate of tetracycline was recorded within a degradation time of 0 min to 120 min. The degradation performance diagram of the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1 is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the degradation rate of tetracycline by NiCo2O4 / MnO2 composite catalyst electrode reached 99.1% within 120 minutes, showing excellent electrocatalytic degradation performance.
[0057] Example 2: The preparation method of the NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics in this example is carried out according to the following steps:
[0058] 1. Cut the Ti substrate into 1cm×3cm samples, immerse them in a constant temperature water bath filled with 40wt% sodium hydroxide solution to remove oil, take them out and use deionized water ultrasonic cleaning to obtain the deoiled Ti substrate; immerse the deoiled Ti substrate in a 10wt% oxalic acid solution for etching, take them out and use deionized water ultrasonic cleaning to obtain a clean Ti substrate;
[0059] 2. 3.75 mmol of cobalt chloride hexahydrate, 1.25 mmol of nickel sulfate hexahydrate, 10 mmol of ammonium chloride and 30 mL of deionized water were mixed, and stirred at a speed of 70 r / min for 30 min to obtain an electrodeposition solution A;
[0060] 3. Mix 7.5 mmol of anhydrous manganese sulfate, 15 mmol of sodium sulfate and 30 mL of deionized water, and stir at a speed of 70 r / min for 30 min to obtain an electrodeposition solution B;
[0061] Preparation of NiCo2O4 intermediate layer: With the clean Ti substrate as cathode and the titanium sheet as anode, the distance between the anode and cathode is 2 cm, and the electrodeposition is carried out in the electrodeposition solution A, wherein the current density during the electrodeposition is 10 mA / cm 2 , the electrodeposition time is 20min, the temperature during electrodeposition is 30℃, and the stirring speed is 60r / min; after the electrodeposition procedure is completed, the electrode is cleaned with clean water and placed in an oven at a temperature of 50℃ for 1 hour to obtain an electrode sheet loaded with a precursor; then the electrode sheet loaded with a precursor is placed in a muffle furnace and calcined at a temperature of 300℃ for 3h to obtain an electrode sheet loaded with a NiCo2O4 catalyst;
[0062] 5. Preparation of MnO2 layer: The electrode sheet loaded with NiCo2O4 catalyst was used as anode and the platinum sheet was used as cathode. The distance between the anode and cathode was 2 cm. Electrodeposition was performed in electrodeposition solution B. The current density of electrodeposition was 15 mA / cm 2 ; The electrodeposition time was 30 min, the electrodeposition temperature was 20 °C, and the stirring speed was 60 r / min; after the electrodeposition procedure was completed, the electrode was cleaned with clean water and dried in an oven at 50 °C for 2 hours to obtain a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics, recorded as NiCo2O4 / MnO2-2.
[0063] Figure 4 The scanning electron microscope image of the NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2; Figure 4 It can be seen that under an electron microscope, the NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2 did not completely form nanosheets compared with the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1, resulting in its specific surface area being smaller than that of the NiCo2O4 / MnO2-1 composite catalyst electrode.
[0064] The NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2 is used to degrade antibiotic wastewater. The specific method is as follows:
[0065] Preparation of tetracycline simulated wastewater: 50 mg of tetracycline solid and Na2SO4 are dissolved in 1 L of deionized water to obtain antibiotic wastewater; the mass fraction of Na2SO4 in the antibiotic wastewater is 1%.
[0066] The NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2 was used as the anode and the stainless steel electrode was used as the cathode. The electrode was inserted into 50 mL of antibiotic wastewater and then heated to 15 mA / cm 2 The degradation was performed at a voltage of 50 V, and the degradation of antibiotics was recorded within 0 min to 120 min. The degradation performance of the NiCo2O4 / MnO2-2 composite catalyst electrode prepared in Example 2 is shown in the figure below: Figure 5 As shown by Figure 5 It can be seen that the degradation rate of tetracycline by NiCo2O4 / MnO2-2 composite catalyst electrode reached 89.4% within 120 minutes, and the electrocatalytic degradation performance was good.
[0067] Comparative Example 1: This comparative example is to prepare a NiCo2O4 electrode sheet, and the specific steps are as follows:
[0068] 1. Cut the Ti substrate into 1cm×3cm samples, immerse them in a constant temperature water bath filled with 40wt% sodium hydroxide solution to remove oil, take them out and use deionized water ultrasonic cleaning to obtain the deoiled Ti substrate; immerse the deoiled Ti substrate in a 10wt% oxalic acid solution for etching, take them out and use deionized water ultrasonic cleaning to obtain a clean Ti substrate;
[0069] 2. 3.75 mmol of cobalt chloride hexahydrate, 1.25 mmol of nickel sulfate hexahydrate, 10 mmol of ammonium chloride and 30 mL of deionized water were mixed, and stirred at a speed of 70 r / min for 30 min to obtain an electrodeposition solution;
[0070] 3. Using the clean Ti substrate as the cathode and the titanium sheet as the anode, the distance between the anode and the cathode is 2 cm, and electrodeposition is performed in the electrodeposition solution obtained in step 2, wherein the current density during electrodeposition is 10 mA / cm 2 The electrodeposition time was 20 min, the temperature during electrodeposition was 30 °C, and the stirring speed was 60 r / min. After the electrodeposition procedure was completed, the electrode was cleaned with clean water and dried in an oven at 50 °C for 1 hour to obtain an electrode sheet loaded with the precursor. The electrode sheet loaded with the precursor was then placed in a muffle furnace and calcined at 300 °C for 3 hours to obtain a NiCo2O4 catalyst electrode loaded.
[0071] Figure 6 The scanning electron microscope image of the NiCo2O4 catalyst electrode prepared in Comparative Example 1; Figure 6 It can be seen that under an electron microscope, the NiCo2O4 catalyst electrode prepared in Comparative Example 1 has a network structure composed of nanosheets, with a smooth surface and no cracks.
[0072] The NiCo2O4 catalyst electrode prepared in Comparative Example 1 was used to degrade antibiotic wastewater. The specific method was carried out according to the following steps:
[0073] Preparation of tetracycline simulated wastewater: 50 mg of tetracycline solid and Na2SO4 are dissolved in 1 L of deionized water to obtain antibiotic wastewater; the mass fraction of Na2SO4 in the antibiotic wastewater is 1%;
[0074] The NiCo2O4 catalyst electrode prepared in Comparative Example 1 was used as the anode and the stainless steel electrode was used as the cathode. The electrodes were inserted into 50 mL of antibiotic wastewater and then heated to 15 mA / cm 2 The degradation was carried out at a voltage of 50 V, and the degradation rate of antibiotic wastewater was recorded during the degradation period of 0 min to 120 min. The degradation performance diagram of the NiCo2O4 catalyst electrode prepared in Comparative Example 1 is shown in FIG. Figure 7 As shown, from Figure 7It can be seen that the degradation rate of tetracycline by NiCo2O4 catalyst electrode within 120 min was only 59.6%.
[0075] Comparative Example 2: This comparative example is to prepare a MnO2 electrode sheet, and the specific steps are as follows:
[0076] 1. Cut the Ti substrate into 1cm×3cm samples, immerse them in a constant temperature water bath filled with 40wt% sodium hydroxide solution to remove oil, take them out and use deionized water ultrasonic cleaning to obtain the deoiled Ti substrate; immerse the deoiled Ti substrate in a 10wt% oxalic acid solution for etching, take them out and use deionized water ultrasonic cleaning to obtain a clean Ti substrate;
[0077] 2. Mix 7.5 mmol of anhydrous manganese sulfate, 15 mmol of sodium sulfate and 30 mL of deionized water, and stir at a speed of 70 r / min for 30 min to obtain an electrodeposition solution;
[0078] 3. Use the clean Ti substrate as cathode and the titanium sheet as anode, with the distance between the anode and cathode being 2 cm, and place them in the electrodeposition solution obtained in step 2 for electrodeposition, wherein the current density during electrodeposition is 15 mA / cm 2 The electrodeposition time was 30 min, the electrodeposition temperature was 50 °C, and the stirring speed was 60 r / min to obtain a loaded MnO2 catalyst electrode.
[0079] Figure 8 The scanning electron microscope image of the MnO2 catalyst electrode prepared in Comparative Example 2; Figure 8 It can be seen that under an electron microscope, the MnO2 catalyst electrode prepared in Comparative Example 2 has larger nanosheets, a smooth surface and no cracks compared to the NiCo2O4 / MnO2-1 composite catalyst electrode prepared in Example 1.
[0080] The antibiotic wastewater was degraded using the MnO2 catalyst electrode prepared in Comparative Example 2, and the specific method was carried out according to the following steps:
[0081] Preparation of tetracycline simulated wastewater: 50 mg of tetracycline solid and Na2SO4 are dissolved in 1 L of deionized water to obtain antibiotic wastewater; the mass fraction of Na2SO4 in the antibiotic wastewater is 1%;
[0082] The MnO2 catalyst electrode prepared in Comparative Example 2 was used as the anode and the stainless steel electrode was used as the cathode. The electrodes were inserted into 50 mL of antibiotic wastewater and then heated to 15 mA / cm 2 The degradation was performed at a voltage of 50 V, and the degradation rate was recorded from 0 min to 120 min. The degradation performance of the MnO2 catalyst electrode prepared in Comparative Example 2 is shown in FIG. Fig. 9 As shown by Fig. 9It can be seen that the degradation rate of tetracycline by MnO2 catalyst electrode within 120 minutes was only 56.1%.
[0083] The degradation rates of the electrode sheets prepared in Examples 1 and 2 and Comparative Examples 1 and 2 are listed in Table 1.
[0084] Table 1 Degradation performance of electrode sheets prepared in Examples 1, 2 and Comparative Examples 1, 2
[0085] sample electrode Degradation rate (%) Example 1 <![CDATA[NiCo2O4 / MnO2-1 composite catalyst electrode]]> 99.1% Example 2 <![CDATA[NiCo2O4 / MnO2-2 composite catalyst electrode]]> 89.4% Comparative Example 1 <![CDATA[NiCo2O4 catalyst electrode]]> 59.6% Comparative Example 2 <![CDATA[MnO2 catalyst electrode]]> 56.1%
[0086] From the comparison in Table 1, it can be seen that the degradation rate of antibiotics by the NiCo2O4 / MnO2 composite catalyst electrode prepared in Examples 1 and 2 is much higher than that of the NiCo2O4 catalyst electrode and the MnO2 catalyst electrode.
[0087] A 1% Na2SO4 solution was prepared as the electrocatalytic electrolyte, and 98% concentrated sulfuric acid was added to adjust the pH value of the solution to 1. The electrode sheets prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used as anodes, and the stainless steel sheet was used as cathodes. A voltage regulator was connected to the electrode sheet at a current density of 500 mA / cm 2 The stability test results are shown in Figure 2. Fig.10 As shown in Table 2:
[0088] Table 2 Accelerated life time of the electrode sheets prepared in Example 1 and Comparative Examples 1-2
[0089] sample electrode Time (min) Example 1 <![CDATA[NiCo2O4 / MnO2-1 composite catalyst electrode]]> 260 Comparative Example 1 <![CDATA[NiCo2O4 catalyst electrode]]> 70 Comparative Example 2 <![CDATA[MnO2 catalyst electrode]]> 140
[0090] It can be seen from Table 2 that at a current density of 500 mA cm -2 Under the extreme conditions of a strong acid environment with a pH value of 1, the NiCo2O4 / MnO2-1 composite catalyst electrode exhibits remarkable durability. Compared with a single NiCo2O4 catalyst electrode or a MnO2 catalyst electrode, the NiCo2O4 / MnO2-1 composite catalyst electrode uses the chemically stable MnO2 as the outer layer, thereby protecting the NiCo2O4 middle layer. The introduction of the NiCo2O4 middle layer can also improve the adhesion of the MnO2 outer layer, thereby increasing its accelerated life time under high stress conditions by 3.7 times and 1.9 times that of a single NiCo2O4 catalyst electrode and a MnO2 catalyst electrode, respectively.
[0091] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics, characterized in that The method proceeds as follows:
1. First, the metal or alloy substrate is degreased and the surface oxide layer is removed in sequence, and then ultrasonically cleaned with deionized water to obtain a clean substrate; 2. Mixing a metal salt, an ammonium salt and a solvent and stirring them to obtain an electrodeposition solution A; wherein the metal salt is a cobalt salt and a nickel salt; 3. mixing the manganese salt, the sulfate and the solvent and stirring them to obtain an electrodeposition solution B; 4. Preparation of NiCo2O4 intermediate layer: using a clean substrate as cathode and a titanium sheet as anode, electrodeposition is performed in electrodeposition solution A; after the electrodeposition process is completed, the electrode is cleaned with clean water and dried to obtain an electrode sheet loaded with a precursor; then the electrode sheet loaded with a precursor is placed in a muffle furnace and calcined at a temperature of 200°C to 500°C for 1h to 5h to obtain an electrode sheet loaded with a NiCo2O4 catalyst; 5. Preparation of MnO2 layer: Using the electrode sheet loaded with NiCo2O4 catalyst as the anode and the platinum sheet as the cathode, electrodeposition is carried out in the electrodeposition solution B. After the electrodeposition process is completed, the electrode is cleaned with clean water and dried to obtain a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics.
2. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1, characterized in that: The cobalt salt described in step 2 is Co(NO3) 2、 The nickel salt is one or more of CoCl2, CoSO4 and CoF2; the nickel salt is one or more of NiCl2, Ni(NO3)2 and NiSO4.
3. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: The ammonium salt described in step 2 is one or more of NH4F, NH4NO3 and NH4NO2.
4. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: Ni in the nickel salt described in step 2 2+ 、Co in cobalt salts 2+ NH4 in ammonium salt + The molar ratio of the substance is (0.01~10)mmol:(0.02~20)mmol:(0.1~100)mmol.
5. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: The manganese salt described in step 3 is one or more of MnSO4, Mn(NO3)2, and MnCl2.
6. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: The sulfate described in step 3 is one or more of Na2SO4, K2SO4, and (NH4)2SO4.
7. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: Mn in the manganese salt described in step 3 2+ SO4 in sulfate 2- The molar ratio of the substance is (0.01~20)mmol:(0.1~100)mmol.
8. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: The electrodeposition described in step 4 is carried out by constant current electrodeposition. During the electrodeposition, the distance between the anode and the cathode is 2 to 3 cm, and the constant current is controlled to be 1 to 50 mA / cm 2 The electrodeposition time is 20 to 25 minutes, and the electrodeposition temperature is 20 to 50°C.
9. The method for preparing a NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics according to claim 1 or 2, characterized in that: The electrodeposition described in step 5 is carried out by constant current electrodeposition. During the electrodeposition, the distance between the anode and the cathode is 2 to 3 cm, and the constant current is controlled to be 5 to 60 mA / cm 2 The electrodeposition time is 30 to 35 minutes, and the electrodeposition temperature is 20 to 50°C.
10. Application of the NiCo2O4 / MnO2 composite catalyst electrode prepared by the method of claim 1 for electrocatalytic degradation of antibiotics, characterized in that The NiCo2O4 / MnO2 composite catalyst electrode for electrocatalytic degradation of antibiotics was used in the degradation of antibiotics.